2013
DOI: 10.1002/jbm.a.34669
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of a new calcium phosphate cement with RGD-chitosan-fiber

Abstract: Calcium phosphate cement (CPC) has been widely used in orthopedic and dental applications. A critical limitation of CPC is low strength and high susceptibility to severe fracture. Surgeons can use it only to reconstruct non-stress bearing bone, raising the need for a tougher new generation of CPC. Fibers have been used as a reinforcement of CPC to improve the strength of a pure CPC scaffold. The RGD peptides (Arg-Gly-Asp) have been used to improve the biocompatibility of the scaffold, via physical adsorption. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
(127 reference statements)
1
19
0
Order By: Relevance
“…Regarding the biological characterization of these materials, a previous study by Wu et al (Wu et al 2013) evaluated the effect of the addition of chitosan fibers in a CPC on osteoblast-like cells. No -16 -differences were observed between the pristine CPC and the FRCPC on cell adhesion, proliferation or viability (up to 14 days of cell culture).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the biological characterization of these materials, a previous study by Wu et al (Wu et al 2013) evaluated the effect of the addition of chitosan fibers in a CPC on osteoblast-like cells. No -16 -differences were observed between the pristine CPC and the FRCPC on cell adhesion, proliferation or viability (up to 14 days of cell culture).…”
Section: Discussionmentioning
confidence: 99%
“…However, these FDA approved antibiotics eluting PMMA bone cements are more appropriate being used as a preventative measure than for the treatment because of their lack of effect on active IRIs due to limited and burst release of embedded antibiotics [57, 58]. Antibiotics release from PMMA cements is mainly due to the diffusion through surface roughness, superficial pores, and surface erosion [46, 58, 59]. The release characteristic of PMMA was typically performed as a biphasic phase which included a burst head of initial release and a continued tail of ineffective release for weeks or months.…”
Section: Main Components Of Coating For Irismentioning
confidence: 99%
“…The calcium phosphate materials are degradable and the end products are calcium and phosphate (Ca 2+ , PO 4 3− ) that are biocompatible, bioactive, and stimulate new bone growth [5962]. The injectable CPCs are now commercial available that can be solidified after implantation.…”
Section: Main Components Of Coating For Irismentioning
confidence: 99%
“…An appreciation however, of their molecular structure indicates this is possible. Others have demonstrated that RGD can promote adhesion and osteoblast activation in relation to a pure calcium phosphate cement (31). It is worth noting that in this application the biological scaffold Chitosan improved the calcium phosphate's properties by a fibre reinforcing mechanism (31).…”
mentioning
confidence: 80%